Effect of exercise on lipid peroxidation - Demir, S; Turgut, G; Yurtseven, O; Aslan, D; Genç, O (Acta medica (Hradec Kralove), 2001)
PURPOSE: The effect of physical exercise on lipid peroxidation was investigated. METHOD: 27 healthy young adult male subjects were included in this study. Urine samples were collected before and after exercises. Urinary malondialdehyde and creatinine levels (Cr) were measured. RESULTS: Urinary malondialdehyde levels were increased by exercise. While pre-exercise malondialdehyde levels were 5.02 +/- 1.26 nmol/mg Cr, post-exercise levels were 6.13 +/- 1.84 nmol/mg Cr (p < 0.05). CONCLUSION: These findings indicated that physical exercise induced lipid peroxidation.
Keywords: dospělí; Exercise; Adult; lidé; cvičení; mladiství; kreatinin; Adolescent; Malondialdehyde; malondialdehyd; Humans; Creatinine; Lipid Peroxidation; mužské pohlaví; Male; peroxidace lipidů